MODERNISASI PESAWAT C-130 HERCULES KERJASAMA PT. GARUDA MAINTENANCE FACILITY AEROASIA TBK DAN PT. DIRGANTARA INDONESIA - Awan Yulianto; Supri Abu; Marsono Marsono (Universitas Perrtahanan Indonesia (UNHAN), 2023)
The existence of PT. GMF AeroAsia Tbk and PT. Dirgantara Indonesia is an important pillar in the national defense industry that can support the interests of the Indonesian Air Force, especially in the process of maintaining and modernizing the C-130 Hercules aircraft. On this basis, this study aims to identify and analyze the synergy of PT. GMF AeroAsia Tbk and PT. Dirgantara Indonesia in the maintenance and modernization of the C-130 Hercules aircraft. The method used in this research is a qualitative method with a case study approach. The data analysis technique used is an interactive data analysis technique. Data collection techniques were carried out through in-depth interviews, observation, as well as literature studies and documentation studies. The data validity technique used is source triangulation. The results showed the synergy of PT. GMF AeroAsia Tbk and PT. Dirgantara Indonesia in the maintenance and modernization of the C-130 Hercules aircraft is carried out by establishing three main pillars of synergy which include sharing, flexibility/stability (error compensation), and task-dependence. First, the sharing pillar is implemented by sharing tasks based on the company's core business and capabilities. The two pillars of flexibility/stability are implemented by complementing each other's capabilities that neither company has. The three pillars of task dependence are carried out based on a memorandum of understanding that has been agreed upon by both parties